2022
DOI: 10.3389/fenvs.2022.993353
|View full text |Cite
|
Sign up to set email alerts
|

The research on the effect of digital economy development on urban air quality

Abstract: Digital economy and air quality are the key issues concerned by the government and academia. The healthy and sustainable development of the digital economy and the continuous optimization of urban air quality are not only conducive to high-quality economic development but also closely related to people’s livelihood. Based on the panel data of 228 cities from 2015 to 2020, using the panel regression and the mediating effect test methods, this paper verifies the impact of the digital economy development on urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Meanwhile, some scholars believe that the impact of the digital economy on air quality is spatially heterogeneous [ 54 ]. Our research shows that the digital economy has a significant negative impact on haze pollution in the middle and lower reaches of the Yellow River Basin, but the impact effect in the lower reaches is greater than that in the middle reaches.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some scholars believe that the impact of the digital economy on air quality is spatially heterogeneous [ 54 ]. Our research shows that the digital economy has a significant negative impact on haze pollution in the middle and lower reaches of the Yellow River Basin, but the impact effect in the lower reaches is greater than that in the middle reaches.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Model (2) illustrates that firms in the northern region exhibit markedly lower CTFP compared to their southern counterparts at the 1% level. Conversely, Model (3) shows that the AQI in the north significantly exceeds that in the south, also at the 1% level. The findings from Model (4), representing the second-stage estimation, confirm a substantial negative impact of air pollution on CTFP at the 1% level, thus strongly supporting H1.…”
Section: Baseline Regressionmentioning
confidence: 87%
“…This observation fully corroborates H2(b). Model (3) shows that air pollution negatively affects investment in technological innovation at the 1% level. Since technological innovation is pivotal for corporate growth and high-quality development, reduced investment in this area, spurred on by air pollution, hampers CTFP enhancement.…”
Section: Expanded Analysis 441 Mediating Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have shown that the digital economy promotes green economic development. For example, Song et al (2022) found that the development of the digital economy can improve urban air quality. Kong and Li (2022) found that the development of the digital economy is helpful in improving the efficiency of a green economy.…”
Section: Impulse Response Analysismentioning
confidence: 99%